Mammalian Polycomb-mediated repression of Hox genes requires the essential spliceosomal protein Sf3b1 - Isono, Kyoichi (Cold Spring Harbor Laboratory Press, 2005)
Polycomb group (PcG) proteins are responsible for the stable repression of homeotic (Hox) genes by forming multimeric protein complexes. We show (1) physical interaction between components of the U2 small nuclear ribonucleoprotein particle (U2 snRNP), including Sf3b1 and PcG proteins Zfp144 and Rnf2; and (2) that Sf3b1 heterozygous mice exhibit skeletal transformations concomitant with ectopic Hox expressions. These alterations are enhanced by Zfp144 mutation but repressed by Mll mutation (a trithorax-group gene). Importantly, the levels of Sf3b1 in PcG complexes were decreased in Sf3b1-heterozygous embryos. These findings suggest that Sf3b1-PcG protein interaction is essential for true PcG-mediated repression of Hox genes.